A Simple Checking Algorithm with Perturb and Observe Maximum Power Point Tracking for Partially Shaded Photovoltaic System - Rozana Alik; Awang Jusoh; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper presents a simple checking algorithm for maximum power point tracking (MPPT) technique for Photovoltaic (PV) system using Perturb and Observe (P&O) algorithm. The main benefit of this checking algorithm is the simplicity and efficiency of the system whose duty cycle produced by the MPPT is smoother and changes faster according to maximum power point (MPP). This checking algorithm can determine the maximum power first before the P&O algorithm takes place to identify the voltage at MPP (VMPP), which is needed to calculate the duty cycle for the boost converter. To test the effectiveness of the algorithm, a simulation model of PV system has been carried out using MATLAB/Simulink under different level of irradiation; or in other words partially shaded condition of PV array. The results from the system using the proposed approach prove to have faster response and low ripple. Besides, the results are close to the desired outputs and exhibit an approximately 98.25% of the system efficiency. On the other hand, the system with conventional P&O MPPT seems to be unstable and has higher percentage of error. In summary, the proposed method is useful under varying level of irradiation with higher efficiency of the system.